1978
DOI: 10.1021/bi00598a008
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of heme a, cytochrome oxidase-ligand complexes, and alkaline denatured oxidase

Abstract: We report 441.6 nm excitation resonance Raman spectra of oxidized and reduced monomeric heme a-imidazole, cytochrome oxidase-exogenous ligand complexes in various redox states, and alkaline denatured oxidase. These data show that, in reduced oxidase, the cytochrome a3 Raman spectrum has bands at 215, 364, 1230, and 1670 cm-1 not observed in the cytochrome a spectrum. The appearance of these bands in the reduced cytochrome a3 spectrum is due to interactions between the heme a of cytochrome a3 and its protein en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
78
3

Year Published

1982
1982
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 23 publications
9
78
3
Order By: Relevance
“…The behavior of the carbonyl stretching mode (1,666 cm-') of the formyl group (21,22) of the cytochrome a3 (see discussion below) is also consistent with complete spectral separation. It is very weak for the CO-bound reduced enzyme with 441.6-nm excitation in Fig.…”
Section: Results and Discus'supporting
confidence: 63%
“…The behavior of the carbonyl stretching mode (1,666 cm-') of the formyl group (21,22) of the cytochrome a3 (see discussion below) is also consistent with complete spectral separation. It is very weak for the CO-bound reduced enzyme with 441.6-nm excitation in Fig.…”
Section: Results and Discus'supporting
confidence: 63%
“…The formyl CdO stretching bands appeared at 1671 cm -1 in the air-oxidized state (a), at 1668 cm -1 in the reduced state (b), at 1667 cm -1 in the CO-reduced state (c), and at 1651 cm -1 in the CNreduced state (d). Corresponding bands had been assigned for heme a 3 of bovine heart cytochrome c oxidase Salmeen et al, 1978) (Table 1). These frequencies are also very similar to those of the corresponding bands of other heme-copper oxidases ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The direct photoreduction of CcO from a variety of sources and by light of different wavelengths has been reported (21–31). Resonance Raman (RR) spectra of the oxidized enzyme obtained by blue excitation closely resembled those of partially reduced CcO; the spectral changes were found to be dependent on acquisition time and laser power (21–23). Ogura et al (25) identified the principal photoproduct as the reduced low‐spin heme a. Babcock et al (28) concluded that heme a is first photoreduced, followed by heme a 3 , but attributed the photoreduction to flavin impurities as originally proposed by Adar and Yonetani (21).…”
Section: Introductionmentioning
confidence: 99%
“…External, low potential reductants react with the enzyme to produce the fully reduced enzyme, as well as a mixture of intermediate, equilibrating oxidation states, depending on the number of reducing equivalents delivered to the enzyme (19,20). Similarly, irradiation of the oxidized enzyme with visible or UV light results in autophotoreduction (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31), a process that is poorly understood (30,31).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation